DETERMINAN KELELAHAN KERJA PADA PEKERJA PABRIK MAKANAN DI MASA PANDEMI COVID-19 TAHUN 2022 - Fina Budi Rahayu (2022)
Work fatigue is a risk that drives work accidents that occur when doing work. Internal and external factors are contributing factors to work fatigue. This study aims to analyze the determinants of work fatigue in food factory workers during the COVID-19 pandemic. This type of research is quantitative analytical research with a cross-sectional approach. The research subjects of the packing division workers totaled 100 people using the purposive sampling method. The research data collection technique uses IFRC questionnaires and measures the height and weight of workers. The datais analyst was performed univariately and bivariately using the Chi Square test. The results of the study found that as many as 70% of workers experienced moderate category work fatigue. The results of the analysis showed that there was a significant relationship between ages (p-value= 0.044; POR=0.36), education level (p-value=0.049; POR=0.13), duration of work (p-value=0.035; POR=3.39), and work shift (p-value=0.023; POR=0.32) with work fatigue. While gender (p-value = 0.280; POR=0.40), marital status (p-value=0.088; POR=0.42), sleep quantity (p-value=0.700; POR=1.34), nutritional status (p-value=0.353; POR=1.69), and length of service (p-value=0.237; POR=0.54) there was no significant association with work fatigue. Therefore, the company must regulate the duration of working hours in accordance with the applicable rules and carry out the division of 3 shifts again.